Two-weeks of single-leg immobilization alters IMCL storage, mitochondrial content, and insulin signalling in healthy, young women - Black, Merryl (University of Waterloo, 2019)
During limb immobilization and bed rest, there is a significant loss of muscle mass and strength, and an onset of insulin resistance (IR). Subcellular localization of intramyocellular lipids (IMCL) is suggested to regulate the metabolic role of IMCL within skeletal muscle. IMCL stored in the subsarcolemmal (SS) region of the muscle fibre is associated with IR. Total IMCL content is unchanged by immobilization, but endurance training has been found to redistribute IMCL from the SS to the intermyofibrillar (IMF) region. Disuse also decreases mitochondrial content and function and can contribute to IR. The aim of the research presented in this thesis was to determine the effects of disuse on IMCL storage location and apposition with mitochondria and whether these changes are related to disuse-induced defects in insulin signalling. We also determined whether omega-3 fatty acid (FA) supplementation alters the effect of disuse on these outcomes. Young, healthy (n=20) women received omega-3 FA supplement (2.97g of EPA and 2.03g of DHA) or a placebo (isoenergetic and volume equivalent of sunflower oil) for 4-weeks prior to and continuing through 2-weeks of leg immobilization and 2-weeks of recovery. Skeletal muscle biopsies were taken prior to supplementation, pre- and post-immobilization, and after recovery. Electron microscopy was used to determine IMCL size, number, area density, and subcellular localization, as well as mitochondrial area density and subcellular localization. Western blotting was used to examine proteins related to insulin signalling, IMCL metabolism, mitochondrial dynamics, and apoptosis-related signalling. There was no effect of omega-3 FA on any measured parameter. IMCL area density decreased in the SS region during immobilization and recovery due to reduced IMCL size. Central IMF IMCL area density increased with immobilization and returned to baseline during recovery. There was a corresponding decrease in mitochondrial content in the SS region during immobilization and in both the SS region and central IMF during recovery. There was no effect of immobilization or recovery on IMCL or mitochondrial characteristics in the peripheral IMF region. PLIN5 and phosphorylated and total AKT content increased during immobilization and remained elevated in recovery. Accumulation of IMCL in the central IMF region is associated with decreased insulin sensitivity (IS). Previous work has found no relationship between SS IMCL content and IR in women, which is supported by the findings of the current study where SS IMCL area density decreased with immobilization. Surprisingly, there was no loss of insulin signalling protein content during immobilization. The differential effects induced by immobilization on insulin signalling in women may be mediated by estrogen and requires further examination.
Keywords: immobilization; IMCL characteristics; mitochondria dynamics; insulin signalling; omega-3 fatty acid supplementation; Insulin resistance; Metabolic syndrome; Extremities (Anatomy); Extremities (Anatomy)--Wounds and injuries; Mitochondria; Insulin; Omega-3 fatty acids